Planificación estratégica universitaria - Vizcarra Herles, Nina Eleonor; Boza Condorena, Edwin Guido (2023)
In the functioning of national universities, political, social, economic, cultural and technological aspects have a direct incidence. Politically, the lack of a national development plan for higher education in the long term is an obstacle to the development of the Peruvian University. In the economic budget, the allocation of the public treasury to the university is less and less. Under these conditions, planning is one of the vital processes of educational administration in this type of institution. This book is important because the difficulties in planning experienced by the organic units of universities can be overcome with proper guidance, institutional strategic planning has not been the subject of substantial research, so this book sought to analyze the characteristics of institutional strategic plans and establish guidelines for a university strategic planning model based on systemic foundations and intelligent organizations.
Keywords: strategic planning; university; intelligent organizations